Diagnostic Value of sST2 in Cardiovascular Diseases: A Systematic Review and Meta-Analysis - Zhang, Tianyi; Xu, Chengyang; Zhao, Rui; Cao, Zhipeng (Frontiers in Cardiovascular Medicine, 2021)
Biomarkers such as BNP, NT-proBNP, cTn, and CK-MB contribute significantly to the diagnosis of cardiovascular disease (CVD). Recent studies have demonstrated that suppression of tumorigenicity 2 (ST2) is associated with CVD, but a meta-analysis of ST2 levels in different CVDs has yet to be conducted. Therefore, the present study aimed to investigate soluble ST2 (sST2) levels in patients with ischemic heart disease (IHD), myocardial infarction (MI), and heart failure (HF). A total of 1425 studies were searched across four databases, of which 16 studies were included in the meta-analysis. The Newcastle-Ottawa Quality Assessment Scale (NOS) values of all 16 studies were ≥ 7. The meta-analysis results indicated that sST2 level was not correlated with IHD (standard mean difference [SMD] = 0.58, 95% confidence interval [95% CI] = 0.00 to 1.16, p = 0.05) or MI (weighted mean difference [WMD] = 0.17, 95% CI = −0.22 to 0.55, p = 0.40), but was significantly associated with HF (WMD = 0.21, 95% CI = 0.04 to 0.38, p = 0.02; I2 = 99%, p < 0.00001). sST2 levels did not differ significantly between patients with IHD or MI and healthy individuals; however, we believe that ST2 could be used as an auxiliary diagnostic biomarker of HF.